THE ROLE OF VISUM ET REPERTUM EVIDENCE IN EXAMINATION OF ACTION CASES ABORTION CRIMINAL (Study of Bantul District Court Decision Number 153/Pid.Sus/2022/PN.Btl) - Kiki Maharani Fadhilah; Tamaulina Br. Sembiring; Sumarno (PT. Radja Intercontinental Publishing, 2024)
This gives rise to the intention to end the pregnancy and this is called abortion. Visum et repertum plays an important role as evidence in the judicial process, especially in abortion cases. The role of Visum et Repertum in determining material truth is very important and important, especially in criminal cases, considering the increasing number of criminals who hide their crimes from the law. The research method uses the qualitative analysis method, which is a way of analyzing data sourced from legal materials based on concepts, theories, statutory regulations or the researcher's own views. The aim of this research is to determine the criminal liability of perpetrators of abortion crimes, the validity of the post mortem et repertum as evidence in the process of proving the crime of abortion and the role of the post mortem et repertum evidence in the examination of abortion crime cases in Bantul District Court Decision Number 153/Pid .Sus/2022/Pn.Btl. In this research, three main theories were chosen to provide a strong and relevant theoretical foundation according to each focus of the chapters discussed, namely grand theory, middle theory and applied theory. This theory is very important because evidence is a fundamental element in criminal law, which plays a role in determining the truth of a criminal incident and identifying the party responsible for the action. Visum et repertum plays an important role in providing objective and scientific evidence to strengthen or evaluate the reliability of other evidence in litigation. The results of this research are: 1) Based on the Indonesian Criminal Code, abortion is a criminal act, except in certain conditions regulated in Articles 299, 346, 347, 348, and 349 KUHP.BTL, the abortion violates applicable legal restrictions and the perpetrator is declared criminally accountable. Courts consider several factors, including the perpetrator's intent and the circumstances in which the abortion was performed outside of legal exceptions, to determine the appropriate punishment for the offense. 2) Visum et repertum plays an important role in determining the crime of abortion, especially in Decision Number 153/Pid. Sus/2022/PN..